Professor Chandra follows his bliss - Rajeev Balasubramanyam 1974- (Vintage, 2019)
"P.R. Chandrasekhar, the celebrated professor of economics at Cambridge, is at a turning point. He has sacrificed his family for his career, but his conservative brand of economics is no longer in fashion, and yet again he has lost the Nobel Prize to a rival. His wife has left him for a free spirited West Coast psychiatrist and relocated to Boulder, Colorado. His son, a capitalist guru with a cult following, mocks his father's life work; his middle daughter, the apple of his eye, has become a Marxist and refuses to speak to him; and his youngest daughter is struggling through her teenage years with the help of psychedelic drugs. And then, the final indignity: He is hit by a bicycle and forced to confront his mortality. Professor Chandra's American doctor instructs him to change his workaholic ways and "follow his bliss"--and so he does, right to the coast of California, and into the heart of his dysfunctional family. Witty, charming, and all too human, Professor Chandra's path to enlightenment will enchant and uplift readers from all walks of life"--